Experiment in education science: experience and perspectives - Rutkienė, Aušra (Lietuvos matematikos rinkinys, 2023)
The article investigates typical educational research mistakes as well as objective and subjective grounds for them. It attempts to hypothetically define methodological procedures which would enable the mitigation of the consequences of mistakes and the achievement of methodologically mature results of educational experimentation. The research has been based on the analysis of experiments in Lithuanian dissertations on education.